IMPLEMENTASI PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN GEOGEBRA PADA MATA KULIAH ANALISIS VEKTOR DITINJAU DARI LOCUS OF CONTROL MAHASISWA - Ahmad Faridh Ricky Fahmy; Nurul Husnah Mustika Sari; Mei Yuniati; Eka Ramanda (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2023)
Locus of Control is a belief of each individual about something that causes success and failure that occurs in an individual. The purposes of this study are 1) to find out how the implementation of geogebra assisted flipped classroom learning during the covid-19 pandemic; 2) to know the learning outcomes and student activeness in terms of locus of control in the vector analysis course for Mathematics Education IAIN Pekalongan students. This research is a qualitative descriptive purposive sampling to determine the subject. The data collection techniques include (1) questionnaires, (2) interviews, and (3) documentation. Based on the results of the study, it was found that 84% of students gave a positive response to the implementation of geogebra assisted flipped classroom learning. Students with internal locus of control obtained the highest scores in all aspects of the assessment. Have a deeper effort in understanding the material and doing assignments or exams. Students with internal-external locus of control get an average score below that of students with internal locus of control. They already possess more effort and quite active in learning. They tried to optimalize in completing their tasks, but sometimes lack of confidence in his abilities. Students with external locus of control got the lowest scores on all aspects of the assessment. There were not active and also late in collecting the assignments. Lack of effort in understanding the material and directions from lecturers were not concerned well.